2010
DOI: 10.1158/0008-5472.can-09-4294
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epidermal Growth Factor Receptor Degradation in Cisplatin-Induced Cytotoxicity in Head and Neck Cancer

Abstract: Cisplatin and its analogues are the most commonly used agents in the treatment of head and neck squamous cell carcinoma. In this study, we investigated a possible role of epidermal growth factor (EGF) receptor (EGFR) phosphorylation and degradation in cisplatin-induced cytotoxicity. Cisplatin treatment led to an increase in initial EGFR phosphorylation at Y1045, the binding site of ubiquitin ligase, Casitas B-lineage lymphoma (c-Cbl), followed by ubiquitination in the relatively cisplatin-sensitive cell lines.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 40 publications
6
55
0
Order By: Relevance
“…These agents induce the suppression of protein levels of ErbB2 and ErbB3 through the ERK and p38 MAPK signaling pathways, suggesting a novel non-canonical mechanism of ErbB downregulation. Ahsan et al (28) previously reported that EGFR degradation serves a role in cisplatin-induced cytotoxicity in head and neck cancer. Preliminary results using a Phos-tag have demonstrated that CDDP induces phosphorylation of ErbB members at multiple non-canonical residues (Park, unpublished); therefore, the identification of novel serine/threonine sites that regulate the degradation of ErbB receptors is essential for understanding the underlying molecular mechanisms of chemotherapy-induced inactivation of these receptors.…”
Section: Discussionmentioning
confidence: 99%
“…These agents induce the suppression of protein levels of ErbB2 and ErbB3 through the ERK and p38 MAPK signaling pathways, suggesting a novel non-canonical mechanism of ErbB downregulation. Ahsan et al (28) previously reported that EGFR degradation serves a role in cisplatin-induced cytotoxicity in head and neck cancer. Preliminary results using a Phos-tag have demonstrated that CDDP induces phosphorylation of ErbB members at multiple non-canonical residues (Park, unpublished); therefore, the identification of novel serine/threonine sites that regulate the degradation of ErbB receptors is essential for understanding the underlying molecular mechanisms of chemotherapy-induced inactivation of these receptors.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, knockdown of EGFR with small interfering ribonucleic acid (siRNA) can induce autophagic cell death independent of receptor tyrosine kinase activity (27). We have also found that EGFR degradation is an important mechanism that regulates chemotherapy-induced cytotoxicity (24, 26). These findings suggest that EGFR receptor degradation may be more effective in producing cytotoxicity of EGFR driven tumors than inhibition of EGFR activity alone.…”
Section: Introductionmentioning
confidence: 87%
“…We and others have found that EGFR degradation increases tumor cell-specific cytotoxicity of chemotherapy and radiotherapy beyond that of EGFR inhibition alone (25)(26)(27). These studies suggest that not just inhibition of EGFR tyrosine kinase activity but down-regulation of EGFR is an important target in cancer therapy (28,29).…”
Section: Discussionmentioning
confidence: 88%